Medical Management of Sexual Assault Survivors at an Academic Medical Center - Sadaf Rowshanrad; Jamie Kneebusch; Sally Rafie (Journal of Women's Reproductive Health, 2016)
Sexual assault is a serious problem in the United States. It is crucial that the medical management of these patients is adequate. The Centers for Disease Control and Prevention (CDC) provides guidelines for appropriate management of these patients. The purpose of this study is to evaluate medical management of survivors of sexual assault at an academic medical center and identify opportunities for improvements in care. We conducted a retrospective, chart review study of patients aged 12 years and older presenting at an academic medical center following sexual assault or rape between 2009 and 2013. Descriptive statistical tests were used to analyze the data. A total of 29 females and 5 males were identified. The majority of patients presented to the medical center within 24 hours of sexual assault or rape and typically presented to the emergency department. Empiric treatment for infections were 8.8% for Hepatitis B, 29.4% for human immunodeficiency virus, 20.6% for gonorrhea, 17.6% for chlamydia, and 8.8% for trichomonas. Among women of reproductive age, 28.0% were provided with emergency contraception. This study found inconsistency in the medical management of sexual assault survivors. Among this small sample size, many patients were not provided with recommended medical treatments. With this knowledge, the medical center plans to implement institutional guidelines and a corresponding order set in the computerized prescriber order entry system to standardize the medical management of sexual assault survivors and educate healthcare professionals. Future studies are warranted to evaluate the impact of standardized guidelines and order set implementation.
Keywords: Rape